EFFECT OF KUFESTROL PREPARATION ON HEN EGG PRODUCTION - G. M. Kuldoshev; M. Rakhimov; R. Kholbutaev; S. Makhmudova (Web of Journals Publishing, 2025)
This article presents data on the effect of the kufestrol preparation on chicken egg productivity and some hematological indicators.